Smiling Gurken gradient: An expansion of the Gurken gradient. - Wang, P.Y.; Chang, W.L.; Pai, L.M. (Fly, 2008)
Morphogen gradients provide unique positional information within a tissue. Cells that are sensitive to the concentration of the morphogen integrate this signal and develop an appropriately distinct cell fate. A morphogen gradient is usually generated by a restricted source and shaped by the speed of diffusion and stability of the signaling molecule. In addition, the availability of receptor and Heparan Sulfate Proteoglycans (HSPGs) help to shape the gradient. We have shown that overexpression of Dally-like protein (Dlp) causes an expansion of Gurken distribution and a loss of cell fates which are specified by high levels of epidermal growth factor receptor (Egfr) signaling. In this article, we discuss how D-Cbl mediated Egfr endocytosis and the levels of Dlp affect the shape of the Gurken gradient.